2000
DOI: 10.1016/s0735-1097(00)00613-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of subcutaneous erythropoietin and intravenous iron for the treatment of the anemia of severe, resistant congestive heart failure improves cardiac and renal function and functional cardiac class, and markedly reduces hospitalizations

Abstract: Anemia is very common in CHF and its successful treatment is associated with a significant improvement in cardiac function, functional class, renal function and in a marked fall in the need for diuretics and hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
488
6
51

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 648 publications
(576 citation statements)
references
References 54 publications
31
488
6
51
Order By: Relevance
“…We found that anemic patients were more physically and mentally fatigued than non-anemic patients and that decreased hemoglobin level predicted the sensation of general fatigue. Because anemia is common in patients with CHF, it is important to recognize the hemoglobin concentration in fatigued patients and, if possible, correct decreased levels in order to reduce fatigue and improve functional status and HRQOL (Silverberg et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We found that anemic patients were more physically and mentally fatigued than non-anemic patients and that decreased hemoglobin level predicted the sensation of general fatigue. Because anemia is common in patients with CHF, it is important to recognize the hemoglobin concentration in fatigued patients and, if possible, correct decreased levels in order to reduce fatigue and improve functional status and HRQOL (Silverberg et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Among older adults, anemia has been associated with a wide spectrum of adverse outcomes (Lipschitz, 2003), including reduced quality of life (Thomas, 1998;Valderrabano, 2000), decreased muscle strength , increased disability , higher risk of Alzheimer's disease (Beard et al, 1997) and increased all-cause mortality among nursing home residents (Kikuchi et al, 2001), and among moderately to severely disabled women living in the community (Chaves et al, 2004). Anemia has also been linked with congestive heart failure (Silverberg et al, 2000) and impaired cognitive function (Nissenson, 1992). The reduction of oxygencarrying capacity of the blood that occurs with anemia may account for fatigue, cardiovascular complications and impaired physical performance (Lipschitz, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…1 In 142 cases of CHF seen in a cardiac outpatient clinic devoted to CHF, 55.6% were found to have anemia as defined as a hemoglobin (Hb) concentration of < 12 g/dL. The more severe the CHF, the more prevalent and severe was the anemia.…”
Section: Initial Observations On Anemia and Chfmentioning
confidence: 99%
“…As mentioned initially, when we corrected the anemia in 26 severe CHF patients, the CHF improved dramatically. 1 In a subsequent randomized controlled (but not double-blind) study, 86 32 such resistant anemic CHF patients were assigned to 2 groups: 16 received the EPO/IV iron combination and the other 16 did not. In the 16 who were treated, the anemia improved and the NYHA and LVEF improved significantly, the serum creatinine did not change, and the rate of hospitalization fell significantly, as did the doses of oral and IV furosemide.…”
mentioning
confidence: 99%